Development and Evaluation of Empowering Education Program for Maternal Fetal Intensive Care Unit (MFICU) Nurses - Jeung Im Kim; Mikyung Park; Gisoo Shin; Insook Cho; So Young Choi; Eun Mi Jun; Yunmi Kim; Sukhee Ahn (Korean Society of Women Health Nursing, 2019)
PURPOSE: This study was conducted to develop an empowering education program for Maternal-Fetal Intensive Care Unit (MFICU) nurses who provide intensive care to high-risk mother and fetus at hospitals, to test effects of the education program on nursing care confidence and nursing knowledge, and to examine program satisfaction. METHODS: This study comprised of 2 phases: program development and evaluation. First, we have followed a process of program development to develop and refine an empowering education program for MFICU nurses through collaborative works among clinical obstetrics and gynecology doctors and nurses and academic nursing professors. Second, the empowering education program was provided to 49 nurses and evaluated from July 5 to 6, 2019. Levels of MFICU nursing care confidence and knowledge were measured. RESULTS: The empowering education program included 18 hours of lectures, discussion, and Q & A, which continued for 2 days. This program significantly improved high-risk maternal-fetal nursing care confidence and knowledge of nurses. The program was well met with nurses' education need and goals, and found to be highly satisfactory. CONCLUSION: The empowering education program was observed to be effective in terms of improve nursing care confidence and knowledge of nurses in MFICU. It is proposed that this program should be open regularly for nurses to obtain and improve their clinical knowledge, confidence, and competency. Further study is needed to develop and run 2-levels of education such as basic and advanced levels based on nurses' clinical background and competency.